PEMBINAAN PAK BAGI REMAJA SMP NEGERI 1 SEMAU SELATAN DI ERA DIGITALISASI - Tri Oktavia Oematan; Maria Indriani Sesfao; Januar Daniel Rohi; Catur Prio Purnomo; Yuniarti Ablelo (Universitas Mataram, 2023)
Technology actually provides many conveniences for people in carrying out various activities. In recent decades, many facilities have been enjoyed thanks to the sophistication they have developed. However, apart from that, technological advances also have a negative influence on people's lives, especially teenagers. Through digitalization, addiction, abuse, and the influence of content can damage teenage behavior. The purpose of this service activity is to provide education and encouragement for the youth of SMP Negeri 1 Semau Selatan so that they can wisely use the technology that is increasingly developing so that it does not damage their character. The method for carrying out PKM,